Ranking and comparing key factors causing time-overruns in on-site construction. Issue 14 (17th November 2022) - Lindhard, Søren M.; Neve, Hasse; Terje Kalsaas, Bo; Møller, Dan Eggert; Wandahl, Søren
Abstract: For years, the construction industry has looked for ways to avoid time-overruns in construction. Despite previous research mapping the factors affecting time performance, site-managers have difficulties in reducing the time-overrun. In order to create a clearer guidance on how to control time-performance, this study investigates the resource related factors because they are within the site-manager's control. Three Case studies were followed and a survey including 36 participants where conducted. Both investigated and ranked the likelihood of delay due to the seven different resource factors. The ranking of the resource factors was identified as: (1) Construction design, (2) Connecting works, (3) External conditions, (4) Work force, (5) Components and materials, (6) Space, (7) Equipment and machinery. The site-manager's focus should be avoiding the factors that most often is found to cause time-overrun, which are construction design and connecting work that constitute about 60% of the time-overruns. The comparison of the studies revealed that construction professionals were unable to distinguish between the less and the low frequent factors causing time-overrun. Future survey studies should take into consideration that construction professionals' preserved reality does not always correspond to the observed reality. Indicators include low variation between factors and limited use of the scale.